2019
DOI: 10.1140/epjc/s10052-019-7081-0
|View full text |Cite
|
Sign up to set email alerts
|

$$H_0$$ tension: clue to common nature of dark sector?

Abstract: The recently sharpened H 0 tension is argued not to be a result of data calibration or any other systematic feature, but an indication for the common nature of dark matter and dark energy. This conclusion is drawn within modified weak-field General Relativity where the accelerated expansion of the Universe and the dynamics of galaxy groups and clusters are described by the same parameter, the cosmological constant. The common nature of the dark sector hence will result in an intrinsic discrepancy/tension betwe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 18 publications
2
62
0
Order By: Relevance
“…In this Letter, we consider the possibility to use the M87* shadow available information to constraint the Schwarzschild-de Sitter (SdS) and Kerr-de Sitter (KdS) BHs, i.e., taking into account the cosmological constant Λ in the metric. The Λ-term in the spherically symmetric metric is arising also in the modified weak-field general relativity (GR) which enables to consider the common nature of the dark energy and dark matter [9][10][11][12]. That approach also suggests a test for the potential deviations from GR having in view of the value of the cosmological constant Λ = 1.11 × 10 −52 m −2 [13] using the gravity lensing observations [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this Letter, we consider the possibility to use the M87* shadow available information to constraint the Schwarzschild-de Sitter (SdS) and Kerr-de Sitter (KdS) BHs, i.e., taking into account the cosmological constant Λ in the metric. The Λ-term in the spherically symmetric metric is arising also in the modified weak-field general relativity (GR) which enables to consider the common nature of the dark energy and dark matter [9][10][11][12]. That approach also suggests a test for the potential deviations from GR having in view of the value of the cosmological constant Λ = 1.11 × 10 −52 m −2 [13] using the gravity lensing observations [14].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the observational indications for the dark matter and dark energy have triggered the study of variety of modified gravity models. Among the considered modified gravity models is the one involving the cosmological constant in the weak-field limit of GR [8][9][10]. Λ acts as second gravity constant along with the Newtonian constant G, as one of the fundamental constants of Universe [11].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of Λ on various effects and the possibility to obtain constraints associated with Λ-term is considered in [16][17][18][19][20]. Particularly, it was shown that the Λ-term is able to provide a solution for the Hubble tension problem [21].…”
Section: Introductionmentioning
confidence: 99%
“…known as the Schwarzschild-de Sitter metric [12]. This metric arises also as the weak-field limit of GR in view of the Newton theorem on the "sphere-point" equivalence [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Within McCrea-Milne cosmology it enables one to consider e.g. the observed galactic flow in the vicinity of the Local Group [18,19]. The appearance of Λ in the above relations can be given a clear group-theoretical background.…”
Section: Introductionmentioning
confidence: 99%